Dynamic Governance Pada Pengelolaan Informasi Publik Di Provinsi Riau - Resa Vio Vani; Meyzi Heriyanto; Mayarni Mayarni (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
The background of this research is that public information management is a process that involves collecting, storing, processing, and disseminating information owned by the government or public institutions to the public in a transparent and accountable manner using dynamic governance theory indicators. This becomes important to analyze when there are rampant corruption cases and declining bureaucratic performance, especially in the Riau provincial government. The aims of this study were (1) to identify the existing conditions of public information management in Riau Province, (2) to analyze the form of Dynamic Governance in public information management in Riau Province, and (3) to identify the challenges of public information management in Riau Province. This is done using qualitative research methods that aim to elaborate a deeper discussion. Therefore the results of the study state that Riau Province has succeeded in properly managing public information in accordance with applicable rules and procedures. The PPID (Information and Documentation Management Officer) as the main manager of public information in the regions, the Riau Province Diskominfotik, and the Information Commission (KI) play an important role in ensuring that public information services are transparent and can be accessed online by the public. The application of Dynamic Governance in the management of public information in Riau Province has been successful and has had a positive impact. Analysis of the Culture, Capabilities, and Change indicators shows significant changes in the management of public information, which makes it more transparent and easily accessible to the public. However, there are several challenges faced in managing public information in Riau Province.